The gut microbiota contributes to changes in the host immune response induced by Trichinella spiralis - Chengyao Li; Yi Liu; Xiaolei Liu; Xue Bai; Xuemin Jin; Fengyan Xu; Hong Chen; Yuanyuan Zhang; Isabelle Vallee; Mingyuan Liu; Yong Yang (Public Library of Science (PLoS), 2023)
The gut microbiota plays an important role in parasite-host interactions and the induction of immune defense responses. Trichinella spiralis is an important zoonotic parasite that can directly or indirectly interact with the host in the gut. Changes in the gut microbiota following infection with T. spiralis and the role of the gut microbiota in host immune defense against T. spiralis infection were investigated in our study. 16S rRNA sequencing analysis revealed that infection with T. spiralis can reduce the diversity of the gut microbiota and alter the structure of the gut microbiota during early infection, which was restored when the worm left the gut. Antibiotic treatment (ABX) and fecal bacterial transplantation (FMT) were used to investigate the role of the gut microbiota in the host expulsion response during infection with T. spiralis. We found that ABX mice had a higher burden of parasites, and the burden of parasites decreased after fecal bacterial transplantation. The results of flow cytometry and qPCR revealed that the disturbance of the gut microbiota affects the proportion of CD4+ T cells and the production of IL-4, which weakens Th2 responses and makes expulsion difficult. In addition, as the inflammatory response decreased with the changes of the microbiota, the Th1 response also decreased. The metabolomic results were in good agreement with these findings, as the levels of inflammatory metabolites such as ceramides were reduced in the ABX group. In general, T. spiralis infection can cause changes in the gut microbiota, and the presence or absence of microbes may also weaken intestinal inflammation and the expulsion of T. spiralis by affecting the immune response of the host. Author summary Due to the complexity of intestinal environment and function, we are interested in the relationship between Trichinella spiralis and the gut microbiota. In our study, we reported the effects of T. spiralis infection on the gut microbiota of the host and gut microbiota intervention in T. spiralis expulsion by influencing the immune status of the host. On the one hand, we demonstrated that the infection of T. spiralis in the intestinal stage could lead to a decrease in the diversity of the gut microbiota and changes in community structure, and these results are conducive to T. spiralis invasion. On the other hand, the gut microbiota plays an important role in T. spiralis infection. The balance of gut microbiota is largely involved in the invasion and colonization of T. spiralis and the state of host immunity. Our findings further elucidated the relationship among host, parasite and gut microbiota, and provided new insights into the prevention and control of T. spiralis. In addition, the study also provides a new basis for the important role of the gut microbiota in pathogen infection and host homeostasis.